Human-Inspired Balancing and Recovery Stepping for Humanoid Robots - Kaul, Lukas Sebastian (Karlsruhe Series on Humanoid Robotics, 2019)
Robustly maintaining balance on two legs is an important challenge for humanoid robots. The work presented in this book represents a contribution to this area. It investigates efficient methods for the decision-making from internal sensors about whether and where to step, several improvements to efficient whole-body postural balancing methods, and proposes and evaluates a novel method for efficient recovery step generation, leveraging human examples and simulation-based reinforcement learning.